Integrating Augmented Reality and Geographic Information Technology to Promote Tourist Attractions in Hua-Hin District, Prachuap Khiri Khan Province - Jattamart, Aungkana; Plangdecha, Parantiya; Sawatpakdee, Tanchanok; Pungpang, Sudyord; Kwangsawad, Achaporn (Journal of Applied Informatics and Technology, 2023)
The pandemic of COVID-19 has directly affected the tourism industry. Moreover, tourists now prefer to plan their own trips and travel independently by searching for information online. Consequently, the tourism industry has adapted by employing technology to attract tourists and increase revenue. The objectives of this research were 1) to develop public relations media for Hua-Hin tourist attractions using augmented reality technology in conjunction with geographic information technology and 2) to assess the acceptance of public relations media use. V-director was used to develop augmented reality (AR) media. ArcGIS Online was used to develop geographic information (GIS) technology tools. Then the online questionnaires were used to evaluate the acceptance of developed media usage. The sample group for assessing the acceptance of public relations media usage consists of 402 internet users. The results demonstrated that 1) users can retrieve location information through public relations media displayed as AR videos and can also search travel routes to tourist attractions using GIS tools and 2) The assessment results of user acceptance indicate that the experiential aspect of travel has the highest average score ( = 4.59).